2017
DOI: 10.1113/ep086433
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms underpinning sympathetic nervous activity and its modulation using transcutaneous vagus nerve stimulation

Abstract: New Findings What is the topic of this review? This review briefly considers what modulates sympathetic nerve activity and how it may change as we age or in pathological conditions. It then focuses on transcutaneous vagus nerve stimulation, a method of neuromodulation in autonomic cardiovascular control. What advances does it highlight? The review considers the pathways involved in eliciting the changes in autonomic balance seen with transcutaneous vagus nerve stimulation in relationship to other neuromodulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
45
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 35 publications
(57 reference statements)
2
45
0
1
Order By: Relevance
“…Moreover, VNS attenuated cardiac remodelling and suppressed sympathoexcitation in a guinea‐pig model of HFpEF induced by constriction of the thoracic aorta leading to chronic pressure overload (Beaumont et al., ). In addition, recent studies in humans have shown that LLTS suppresses sympathetic nerve activity (Clancy et al., ; Deuchars et al., ). Notably, LLTS inhibited noradrenaline release from cardiac sympathetic nerves, dilated cardiac microcirculatory vessels and increased exercise tolerance in patients with coronary artery disease (Zamotrinsky, Afanasiev, Karpov, & Cherniavsky, ; Zamotrinsky, Kondratiev, & de Jong, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, VNS attenuated cardiac remodelling and suppressed sympathoexcitation in a guinea‐pig model of HFpEF induced by constriction of the thoracic aorta leading to chronic pressure overload (Beaumont et al., ). In addition, recent studies in humans have shown that LLTS suppresses sympathetic nerve activity (Clancy et al., ; Deuchars et al., ). Notably, LLTS inhibited noradrenaline release from cardiac sympathetic nerves, dilated cardiac microcirculatory vessels and increased exercise tolerance in patients with coronary artery disease (Zamotrinsky, Afanasiev, Karpov, & Cherniavsky, ; Zamotrinsky, Kondratiev, & de Jong, ).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the anti-adrenergic effects of VNS have been shown to impact basal and reflex function within the intrinsic cardiac nervous system . In light of the autonomic imbalances and impaired autonomic reflexes in HFpEF (Deuchars et al, 2018;Grassi et al, 2009), which in turn are associated with adverse neural remodelling in multiple neural circuits within the neural hierarchy for cardiac control, we speculate that LLTS targets specific elements within the intrinsic cardiac autonomic nervous system to stabilize excessive reflex responses, which are responsible for disease progression (Florea & Cohn, 2014), thereby mitigating efferent output. It is also likely that LLTS improves diastolic function by both a direct effect on the myocardium related to inflammation and by reducing BP through its anti-adrenergic effects.…”
Section: Discussionmentioning
confidence: 99%
“…The device is similar in construction to the NSS-2 Bridge device which served as the predicate for its approval. (source) (VII), and glossopharyngeal (IX) nerves have been proposed to mediate this type of response (Deuchars et al 2018), suggesting the activation of the parasympathetic nervous system as the core basis of the device function. It has been shown that within 20 min of activation of this device, up to 62.7% reduction of withdrawal symptoms is appreciable, while 84.6% symptoms alleviation has been observed at the end of 60 min (Miranda and Taca 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Deuchars et al. () give an overview of factors such as gap junctions (Lall et al., ), which contribute to the control of the sympathetic activity in health and disease. They then present new data on how autonomic balance can be modulated in humans.…”
mentioning
confidence: 99%
“…The symposium also discussed the application of new autonomic neuromodulation techniques designed to restore sympathetic-parasympathetic balance and limit the pathophysiological consequences of autonomic dysfunction. Deuchars et al (2018) give an overview of factors such as gap junctions (Lall et al, 2017), which contribute to the control of the sympathetic activity in health and disease. They then present new data on how autonomic balance can be modulated in humans.…”
mentioning
confidence: 99%